Alkali-aggregate reaction in recycled aggregate concrete. (10th May 2020) - Peng, Ziyi; Shi, Caijun; Shi, Zhenguo; Lu, Bao; Wan, Shu; Zhang, Zuhua; Chang, Jun; Zhang, Tingting
Abstract: Using recycled concrete aggregate (RCA) to substitute original aggregate (OA) is of significance for sustainable development of construction materials. However, uncertainties remain with respect to the long-term durability of concrete containing RCA. This review article focuses on alkali-aggregate reaction (AAR) of RCA concrete and provides a comprehensive overview of the progress of this subject. The review includes comparison of AAR between RCA and OA concretes; the factors influencing the AAR in RCA concrete; the mitigation measures and the applicability of different test methods for assessing the alkali reactivity of RCA. The reactivity of OA and the remaining reactive component available for secondary AAR in RCA play the essential role in influencing the AAR in concretes containing RCA. In contrast to OA, it is more complicated to assess the AAR potential of RCA due to the variations of the residual mortar (RM) content. Highlights: AAR performance of recycled concrete is affected by many factors. AAR expansion of RCA concrete is not necessarily lower than its parent concrete. AAR potential of RCA is determined by the alkali reactivity of OA and the AAR extent of parent concrete. The efficiency of SCMs to mitigate AAR is lower for RCA concrete than for the OA concrete. Carbonation treatment and suction of pozzolanic materials into RM can mitigate AAR of RCA concrete.